Respostas agronômicas e morfofisiológicas do girassol ao déficit e excesso hídrico em dois solos - Loose, Luís Henrique (2016)
Soil water availability is one of the major factors affecting the success or failure of an agricultural crop. Stresses caused by water deficit or surplus are harmful to the growth and sunflower yield. Plant growth pattern is changed and the yield is reduced with the growth of the intensity corresponding to stress. The main aims of this study were to evaluate the grain yield and quality of sunflower oil, root growth, deepening and distribution of roots in the soil, growth of shoot and roots in dry matter and modeling of sunflower plant growth, in response to stress caused by water surplus and water deficit in two sowing dates and two soils of Rio Grande do Sul. The experiments were carried out at early sowing date (sowing in early September) and late sowing date (sowing in early January), in two soils in the municipalities of Santa Maria (Ultisol) and Panambi (Oxisol). Three treatments of water availability were applied: water deficit (maintaining soil moisture between 40 and 60% of the available water capacity (AWC)), water surplus (maintained between 90% of AWC and the determine saturation point) and control (maintained between 75 and 100% of the AWC). To determine the water condition of the soil along the cycle was held daily sequential water balance. The water inlet by rain in the treatment of water deficit was controlled. The analyzed variables were yield and yield components, oil content and oil yield, fatty acid profile, root depth, root distribution, dry matter of different plant parts, in addition to intrinsic variables of growth analysis. Modeling of the root depth and sunflower growth in dry matter was held of different plant parts. The drought level applied was more harmful than the level of water surplus applied, with significant reduction in yield, yield components and sunflower growth. Sowing date had influence on yield, where the early sowing date produced more than late sowing date. Soil had great influence on the root deepening which was higher in Ultisol compared to Oxisol, which impacted the yield gap under water deficit. Water deficit was responsible for increased Oleic Acid and reduction of Linoleic Acid. The sowing at early sowing date enables deepening and increased dry matter production of roots than sowing at late sowing date. Sunflower growth models in dry matter and root depth had good fit to the measured data. In this way, it is concluded that soil water availability and sowing dates influences the yield and quality of sunflower and should be taken measures to mitigate the problems caused.